2014
DOI: 10.1007/s10554-014-0382-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high-normal blood pressure on left ventricular mechanics: a three-dimensional and speckle tracking echocardiography study

Abstract: To assess the presence of subclinical left ventricular myocardial dysfunction in subjects with high-normal blood pressure (BP) and untreated arterial hypertension, using three-dimensional (3D) echocardiography strain analysis. This cross-sectional study included 49 subjects with optimal BP, 50 subjects with high-normal BP, and 50 newly diagnosed untreated hypertensive patients matched by gender and age. All the subjects underwent 24 h blood pressure monitoring and complete two-dimensional and 3D echocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 39 publications
5
37
0
Order By: Relevance
“…Values were comparable with data from a study including healthy and normotensive power-endurance athletes [24]. For patients with high-normal BP or hypertension, both significantly lower values for left ventricular global strain [24,25] and values comparable to normotensive patients [26] have been published. Probably, the time course of BP elevation plays an important role for the impact on left ventricular mechanics.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Values were comparable with data from a study including healthy and normotensive power-endurance athletes [24]. For patients with high-normal BP or hypertension, both significantly lower values for left ventricular global strain [24,25] and values comparable to normotensive patients [26] have been published. Probably, the time course of BP elevation plays an important role for the impact on left ventricular mechanics.…”
Section: Discussionsupporting
confidence: 80%
“…Probably, the time course of BP elevation plays an important role for the impact on left ventricular mechanics. Athletes in our study were younger compared to patients with high-normal BP and reduced left ventricular global strain (42 AE 8 vs. 47 AE 7 years, respectively) [25]. An elevated BP may induce a deterioration of diastolic function that precedes the reduction of systolic function.…”
Section: Discussionmentioning
confidence: 62%
“…Global area strain (GAS) has been proved to detect early LV systolic dysfunction in athletes, in patients after heart transplantation or after anthracycline therapy, as well as in patients with diabetes and autoimmune disorders [610]. Of note, 3D-STE turned out to be less time consuming than 2D in respect to the acquisition and analysis time [11, 12], thus the former has a greater chance to be routinely used in the clinical practice. The aim of our study was to assess whether 3D-STE provides any new information on myocardial deformation in subjects with optimal repair of CoA.…”
Section: Introductionmentioning
confidence: 99%
“…However, the difference in WMSI was not significant between the non-MI segment group and control group. Although no reduced motions of the non-MI segments were observed visually, myocardial [25], and the significantly reduced GLS, GCS, GRS and GAS seen in subjects with high-normal blood pressure suggesting subclinical myocardial dysfunction [26]. It has also been suggested that GLS may be a sensitive indicator of LV systolic dysfunction in patients with diabetes mellitus even when they demonstrate a normal LVEF [27].…”
Section: Discussionmentioning
confidence: 94%